The Kew book of sugar flowers how to make beautiful floral cake decorations - Brown, Cassie; Spence, Eddie; Royal Botanic Gardens, Kew (Tunbridge Wells, Kent Search Press, 2018)
In the Kew Book of Sugar Flowers, sugarcraft specialist Cassie Brown teaches you how to craft stunning, authentic-looking flowers and foliage using flower paste (gum paste). Learn how to create beautiful bouquets and stunning sprays, from the early stages of germinating your ideas - taking inspiration from nature and making moulds from real flowers and leaves - to creating floral cake decorations with an exotic or wild flower theme for a special occasion
"Royal Botanic Gardens, Kew"--Cover
Includes index
1
Keywords: Artificial flowers; Cake decorating; Cake decorating; Sugar art; Sugar art